A Guide to external evaluation for accreditation of schools of nursing / department of nursing education in the Commonwealth Caribbean - Barker, Maria (PAHO/WHO Washington, DCUS, 1999)
Presents guidelines for the conduct of the external evaluation of nursing education programmes in the Commonwealth Caribbean.